The Impact of Living Arrangement to Elderly Nutritional Health Status in Jember - Sofia Rhosma Dewi (Poltekkes Kemenkes Kupang, 2022)
Introductions: Nutrition has an important role in maintaining the elderly’s health status. The living arrangement is one of the external factors affecting access to food. This study aims to determine the impact of living arrangements on the nutritional status of the elderly. Method: It is a correlational study with a cross-sectional approach. A total of 103 elderly were involved through a consecutive sampling technique. A questionnaire and MNA were used to collect the data, and a chi-square test was used to answer the hypothesis. Result: Statistical analysis results p-value of 0.000 smaller than α 0,05 with RR 11,458 95% confidence interval. Analysis: This means that the living arrangement impacts the elderly nutritional status, and the elderly who live alone are at 11,458 greater risks of experiencing malnutrition than the elderly who live with their families. Discussion: Being engaged with the family provides social support for them. Social interaction needs to be improved so that the elderly will create a positive coping mechanism, enjoy the taste of the food, and have a better quality of life.